KEBIJAKAN FISKAL INDONESIA DALAM MENGHADAPI KETIDAKPASTIAN GLOBAL DAN INFLASI SAAT INI - Apriliantoni, Apriliantoni; Apriliantoni, Rasyad Fiqry Caturitama; Novita Indriyani (Cahaya Ilmu Bangsa, 2024)
For the Indonesian economy, globalization and inflation are significant challenges. The purpose of this study is to analyze Indonesia's economic policies in relation to global and inflationary economic trends, as well as their impact on national economic stability. Pengendalian inflasi, penghapusan ekstrem kemiskinan, penurunan prevalensi penghambatan, and peningkatan investasi domestik are only a few of the quantitative measures that the government has implemented. In addition, APBN is used in a fun way as a tool to monitor public purchasing patterns and macroeconomic stability. Through strong coordination between the national government, regions, and financial institutions, Indonesia has managed to boost economic growth despite facing geopolitical and economic challenges around the world. According to this study, implementing sound and responsible financial management practices can be the most important factor in creating stable and long-lasting economic transformation.